PENERAPAN METODE DRILL UNTUK MENINGKATKAN KEMAMPUAN MENYANYIKAN LAGU DAERAHNUSANTARASISWA KELAS V SDN 119 PEKANBARU - Antosa, Zariul Antosa; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem of this research is to improve the ability to sing folk songs archipelago Elementary School fifth grade students 119 Pekanbaru in learning the art of music with the application of the method Drill. Learning the art of music in this school only to learn the material just never do direct practice. This is due to the lack of teacher knowledge about the art of music. In any learning activity, the teacher just use a lecture or explain any material. In learning the art of music performed by lecture method simply makes children become passive in learning. So that the formulation of the problem in this research is: